Decision Support System For Providing Customer Reward Using Profile Matching Method: A Case Study at PT. Atlas Jakarta - Dedi Saputra; Fajar Akbar; Lisnawanty; Martias; Aan Rahman (Bulletin of Computer Science and Electrical Engineering, 2021)
The proliferation of goods delivery services business makes business competition increasingly tight. It takes the right strategy in increasing the number of customers and increasing profits. One of the strategies that is usually applied is to given appreciation in the form of reward to one of the best customers. This research, aims to facilitate the company PT. Atlas Jakarta in determining the best customers to be rewarded. Metode used is a profile matching method that can be used as one of the supporters of decision PT. Atlas Jakarta in determining its best customers. Profile matching is a mechanism in making a decision by assuming that there is an ideal level of predictor variables that must be met by the subjects studied, not only a minimum level that must be met or passed. In the profile matching method of assessment and calculation of GAP value based on the intensity of delivery, the number of shipments, the length of subscription, and the status of payments. The last step of the profile matching method is the ranking an which shows that the higher the ranking result, the more likely itis for customers to receive rewards. The results showed that with profile matching method can be implemented in a decision support system to determine the reward to customers and facilitate PT. Atlas in making decisions according to the criteria that have been determined.